Can adapalene be repurposed for melanoma? - Nasir, Aiman (Journal of the Pakistan Medical Association, 2023)
Madam, Melanoma, the most lethal skin cancer, accounts for 75% of deaths by skin cancer in the US.1 Nivolumab, Pembrolizumab, and a combination of Nivolumab and ipilimumab are used in adjuvant therapy for distant metastatic melanoma.2 The combination therapy of ipilimumab and nivolumab for melanoma per patient per month was estimated to be USD 71,689.3 Nevertheless, the efficiency of these treatments is limited.4 Furthermore, metastasis can reduce the effectiveness of cancer treatment. With time, cancer cells can also develop resistance to drugs. Hence alternative treatment regimens should be identified.5 The development of new therapies requires a vast amount of time, research, and investment. Drug repurposing provides an alternate approach to this passage. It refers to the new application of previously approved drugs. This process is rapid, potentially safer, and cost-effective.5 Continue...